Ancestral role of Pax6 in chordate brain regionalization - Kozmik, Zbynek; Kozmikova, Iryna (Frontiers in Cell and Developmental Biology, 2024)
The Pax6 gene is essential for eye and brain development across various animal species.Here, we investigate the function of Pax6 in the development of the anterior central nervous system (CNS) of the invertebrate chordate amphioxus using CRISPR/Cas9-induced genome editing. Specifically, we examined Pax6 mutants featuring a 6bp deletion encompassing two invariant amino acids in the conserved paired domain, hypothesized to impair Pax6 DNAbinding capacity and gene regulatory functions. Although this mutation did not result in gross morphological changes in amphioxus larvae, it demonstrated a reduced ability to activate Pax6responsive reporter gene, suggesting a hypomorphic effect. Expression analysis in mutant larvae revealed changes in gene expression within the anterior CNS, supporting the conserved role of Pax6 gene in brain regionalization across chordates. Additionally, our findings, along with established research on hemichordates and vertebrates, support the presence of a zona limitans intrathalamica (ZLI)-like region in amphioxus. This ZLI-like region acts as a critical signaling center and establishes a boundary between major thalamic regions, reinforcing the concept of evolutionary continuity in brain patterning mechanisms.